Treatment goals for patients with schizophrenia: a narrative review of physician and patient perspectives - Gründer, Gerhard; Bauknecht, Philipp; Klingberg, Stefan; Leopold, Karolina; Paulzen, Michael; Schell, Stefanie; Stengler, Katarina; Leucht, Stefan (Pharmacopsychiatry, 2021)
Introduction There are many possible treatment goals for patients with schizophrenia. Two major perspectives on treatment goals are the patient’s and the physician’s perspective. Patient-centered treatment mandates that an individual patient’s treatment goals are taken into account when treatment is planned. In this narrative review, we address the commonalities and differences of the patient’s and physician’s perspectives. Methods We searched for literature on treatment goals for patients with schizophrenia from the last 10 years. Results Fifty-two relevant records were identified, 4 of which directly compare patient’s and physician’s perspectives. Two further articles used the same set of goals to ask patients or physicians for their assessment. Discussion Agreement between patients and physicians regarding valuation of treatment goals was high. However, physicians tended to put more emphasis on the classical “textbook” goals of symptom resolution and functioning, while patients stressed well-being and quality of life more. Results on treatment goals from patients are difficult to generalize, since recruiting representative patient samples is challenging and patient subgroups may have differing priorities.
Publikationsdatum: 08. Dezember 2020 (online)
Gesehen am 18.08.2021